Dispersão mineralógica e geoquímica em crostas e solos lateríticos aplicada à caracterização do substrato do complexo de Maicuru-Pará - ANGÉLICA, Rômulo Simões (Universidade Federal do Pará, 2023)
Maicuru is a typical ultramafic-alkaline-carbonatite complex, located in the NW portion of the state of Pará, intrusive in the granodioritic gneisses of the Guiana craton. Over its rocks, a thick lateritic profile enriched in aluminum and titanium phosphates in the form of anatase has developed. The research rights over the Maicuru area belong to the Docegeo company, which has carried out research work since 1985, involving geochemical prospecting, geological mapping, boreholes, wells, among others. The main objective of the present work was, through the study of the geochemistry and mineralogy of the surface laterites (ferruginous crust and lateritic soils) of Maicuru, to identify the lithological nature of its substrate, in addition to establishing criteria for the geochemical prospecting of these materials under conditions of lateritic weathering under humid tropical forest. The ferruginous crust occupies the central portion of the complex, being differentiated into at least three major units, related to the primary lithology: magnetic crust (with maghemite, ilmenite and anatase), titaniferous crust (with abundant anatase) and phosphate crust, where the aluminum phosphates. The soils border the central structure, with a part derived from the crust itself and another from the primary rocks. The geochemical prospecting carried out by Docegeo consisted of sampling, in a semi-regular mesh of 100 x 200 m, around 1500 surface samples (ferruginous crust and soils), analyzed by this company for the elements Fe203 (total), Ti02, P205 Mn , Ni, Co, Cr, Cu, Pb and Zn. For this thesis, the elements Ba, Ga, Nb, Sc, V, Y and Zr were also analyzed in a second mesh (300 x 400 m), with about 170 samples, and the rare earth elements, in a third mesh , equivalent to half of the samples of the second one. All these data were grouped according to soils and crusts, with the aim of outlining geochemical differences between these two materials, and treated with statistical programs for compatible IBM-PC/XT microcomputers, performing: calculations of basic statistics; analysis of frequency distributions through histograms and cumulative curves, with separation of different populations; construction of correlation matrices and dendrograms of cluster analysis in R-Mode and Q-Mode; estimate of background values and thresholds and construction of surface geochemical maps. Regarding mineralogy, X-ray diffraction studies were carried out on the samples from the 2nd mesh, with the objective of carrying out a semi-quantitative analysis, in addition to studying the dispersion of the main lateritic minerals on the surface. Among the main identified minerals, the following stand out: iron oxy-hydroxides (goethite, hematite, maghemite, ilmenite), titanium (anatasium and ilmenite) and aluminum (gibbsite), which are mainly found in the crusts, in addition to clay- minerals from the kaolinite group, quartz, and aluminum phosphates (especially those from the crandalite group, more frequent in soils). In comparison with other laterites, the crusts and soils of Maicuru have very high average contents of Ti02, P205, Cr, Ba, Sr, Nb, REE and Zr and partly Ga, Sc, Y and V. The ferruginous crusts stand out due to the high levels of Fe 203, Ti02 and P205. Titanium is largely related to anatase (and to a lesser extent to ilmenite) where this mineral derived from titanites and perowskites, characterizing the presence of carbonatites in the Maicuru substrate. Phosphorus, on the other hand, is related to Al-phosphates, characterizing the primary mineralization in apatite, where these minerals are the major carriers of the elements Ba, Sr, Sc, Y and ETR, in addition to Nb and Zr. The soils have higher levels of Al203 and loss on fire, related to clay minerals, gibbsite and Al-phosphates. The anomalous zones obtained for P205 and Ti02 coincided with those delimited by Docegeo, while the background populations of the elements of the 1st grid defined the complex-nesting contact. Other anomalous zones for Nb (which occurs associated with Ti02) and Zr-Ga-Sc were also identified, and although apparently not of greater prospective or economic interest, they showed great significance in the lithological interpretation of the substrate. In addition to these, there were several small anomalous zones in Cu, scattered throughout the crust (especially in the phosphate crust), which may indicate the presence of mineralization in the sub-surface. In the crust, the geochemical associations studied stand out in three large groups, closely related to the three types of ferruginous crusts, where this differentiation is a direct consequence of the lithological variations of the substrate, in which ultramafic-alkaline and carbonatite rocks, partially mineralized, dominate in apatite, titanite and perowskite. Soils, on the other hand, present broader groupings, reflecting a greater process of dispersion through weathering on these three types of crusts and on primary rocks. The geochemical associations studied, especially the two large associations, led by P205 and Fe203, highlight the influence of mineralogy based on iron oxides and hydroxides and Al phosphates, which serve as carriers of the main trace elements that prove the ultramafic- alkaline-carbonatite of the complex. This restriction to P205 and Fe203 shows that Ti02, although present in high levels, does not constitute an expressive geochemical signature. Ferruginous crusts and soils are, in short, from the mineralogical and geochemical point of view, different lateritic materials, and therefore must be treated differently, in terms of geochemical prospecting, as well as the different horizons of a lateritic profile. Prospecting in these lateritic materials, especially in the crusts, should be encouraged – mainly due to their great areal representation in the Amazon – since these can behave like the mimeralized “bedrock” itself, for example, for P, Ti, Fe, Nb, REE and resistatos, in addition to reflecting the lithological nature of the substrate, of great importance in geological mapping.